The Relationship Between Family Support and Anxiety Levels of Preoperative Patients at Daya Regional General Hospital, Makassar City - Sri Resky Mustafa; Rindani Claurita Toban; Ardo Gustap Kapsiang; M. Alfian Rajab; Rusli Taher; Saharuddin Mustafa (Kiara Group, 2026)
Background: Family support refers to the attitudes, actions, and acceptance shown by family members toward a sick individual. Family members perceive supportive individuals as those who are always ready to provide help and assistance when needed. Anxiety is a part of human life characterized by feelings of fear or deep and persistent worry. Objective: This study aimed to determine the relationship between family support and the anxiety levels of preoperative patients at Daya Regional General Hospital, Makassar City. Methods: This study used a quantitative method with a cross-sectional approach. The study population consisted of 926 individuals, with a sample of 30 respondents selected using accidental sampling technique. Results: The Chi-Square test results showed a p-value < 0.05, indicating that there is a relationship between family support and the anxiety levels of preoperative patients at Daya Regional General Hospital, Makassar City.